RISIKO PERBANKAN DENGAN ALTMAN Z SCORE : KAJIAN PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Poppie Indriyanti (Majalah Ilmiah Bijak, 2016)
Abstract. This research was conducted to find out banking risk with Altman Z Score on conventional banks listed on Indonesia Stock Exchange. The data used in this study is secondary data obtained from the annual financial statements of conventional banks during the period 2003-2016 contained in the official website of the Indonesia Stock Exchange.The focus of research (research focuses) on the topic that has been studied is the risk of banking based on Altman Z Score. Of the four studies examined, the equation is all research using quantitative research approach. It means to assess the Altman Z-Score in observing banking risk, the quantitative approach is the most appropriate approach.Of the four studies, the results show banking risk with Altman Z Score, from 2003-2016 the banks listed on the Indonesia Stock Exchange are generally in the category of bankrupt. However, Ganesha et al (2012) study shows the Z value model in 2003-2006 can not show a good enough accuracy level when measured per year. Irwansyah's research (2017) shows that in the period 2013-2016, only one bank, namely Bank Jtrust Indonesia Tbk (BCIC bank code) entered into the healthy category. In addition, Bank Mandiri (Persero) Tbk with BMRI bank code, has started to increase from the predicted category of bankruptcy to the prediction of gray area category.